Inflamm-Aging: A New Mechanism Affecting Premature Ovarian Insufficiency. (2nd January 2019) - Huang, Yaoqi; Hu, Chuan; Ye, Haifeng; Luo, Ruichen; Fu, Xinxin; Li, Xiaoyan; Huang, Jian; Chen, Weiyun; Zheng, Yuehui
Abstract : The normal function of ovaries, along with the secretion of sex hormones, is among the most important endocrine factors that maintain the female sexual characteristics and promote follicular development and ovulation. Premature ovarian insufficiency (POI) is a common cause in the etiology of female infertility. It is defined as the loss of ovarian function before the age of 40. The characteristics of POI are menstrual disorders, including amenorrhea and delayed menstruation, accompanied by a raised gonadotrophin level and decreased estradiol level. Inflammatory aging is a new concept in the research field of aging. It refers to a chronic and low-degree proinflammatory state which occurs with increasing age. Inflammatory aging is closely associated with multiple diseases, as excessive inflammation can induce the inflammatory lesions in certain organs of the body. In recent years, studies have shown that inflammatory aging plays a significant role in the pathogenesis of POI. This paper begins with the pathogenesis of inflammatory aging and summarizes the relationship between inflammatory aging and premature ovarian insufficiency in a comprehensive way, as well as discussing the new diagnostic and therapeutic methods of POI.